Evening and night work schedules and children's social and emotional well-being - Kaiser, T.; Li, Jianghong; Pollmann-Schult, M. (Routledge, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group An emerging body of evidence shows that parents’ non-standard work schedules have a detrimental effect on children's well-being. However, only a limited number of studies have investigated mediating factors that underpin this association. Likewise, only a few studies have examined the impact of fathers’ non-standard work schedules on children's well-being. Based on data from the Families in Germany Study (FiD), this study aimed to address these research gaps. The sample consists of parents and their children at ages 7–8 and 9–10 (n?=?838 child observations in dual-earner families). The data were collected in the years 2010–2013. Non-standard work hours were defined as working in evenings and or at night (every day, several times a week, or changing as shifts). Children's social and emotional well-being was measured with the Strengths and Difficulties Questionnaire (SDQ). The findings show that both mothers’ and fathers’ evening and night work schedules are linked to an increase in children's externalizing and internalizing behavior and that this association is partially mediated by mothers’ and fathers’ harsh and strict parenting, with a stronger mediation effect for fathers parenting.